Cover Picture: Benzene Triimides: Facile Synthesis and Self‐Assembly Study (Chin. J. Chem. 7/2019). Issue 7 (17th June 2019) - Tuo, De‐Hui; He, Qing; Wang, Qi‐Qiang; Ao, Yu‐Fei; Wang, De‐Xian
Abstract : The cover picture shows an efficient one‐pot condensation of maleimide derivatives in the presence of acetic acid and water to afford a series of benzene triimides (BTIs). The structure, physicochemical properties and electrochemistry behavior of BTIs were systematically investigated. Owing to the planar structure and unique electron‐deficient nature, BTIs can self‐assemble into different motifs. More details are discussed by Wang et al . on page 684–688. Abstract : The cover picture shows an efficient one‐pot condensation of maleimide derivatives in the presence of acetic acid and water to afford a series of benzene triimides (BTIs). The structure, physicochemical properties and electrochemistry behavior of BTIs were systematically investigated. Owing to the planar structure and unique electron‐deficient nature, BTIs can self‐assemble into different motifs. More details are discussed by Wang et al . on page 684–688.